2019
DOI: 10.1590/1413-81232018241.06132017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with alterations of the temporomandibular joint in institutionalized elderly

Abstract: Prevalence and factors associated with alterations of the temporomandibular joint in institutionalized elderlyPrevalência e fatores associados a alterações na articulação temporomandibular em idosos institucionalizados Resumo O objetivo deste artigo é avaliar a prevalência e os fatores associados a alterações na ATM em idosos institucionalizados. Estudo observacional e transversal, conduzido em 1.192 idosos brasileiros. Foram realizados exames intra e extraoral, baseados na Ficha de Avaliação da OMS (1997). Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 15 publications
(28 reference statements)
1
21
2
4
Order By: Relevance
“…Two study series reported on periodontal problems for various ages. A Brazilian study series [42,61,65] indicated that the prevalence of periodontitis was 20.6% in residents older than 64 years, whereas the prevalence was 45.7% for residents who were 75 to 84 years old. A lower prevalence of 14.3% was observed for residents who were 95 years old or older.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two study series reported on periodontal problems for various ages. A Brazilian study series [42,61,65] indicated that the prevalence of periodontitis was 20.6% in residents older than 64 years, whereas the prevalence was 45.7% for residents who were 75 to 84 years old. A lower prevalence of 14.3% was observed for residents who were 95 years old or older.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, 11 studies [21,22,24,30,32,33,34,36,38,42,45] explored the association between gender and oral problems or a poor OHRQoL. Three study series [32,38,42,49,58,61,65] reported that the male gender was associated with dental/periodontal problems. Janssens et al [32,49] reported that male Belgian dentate residents had a higher proportion of decayed teeth according to a mixed-effect logistic regression analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations